The role of shopping centres in the metropolization process in Fortaleza (Brazil) and Lisbon (Portugal) - Gonçalves, Tiago Estevam (2020)
Considering that shopping centres are increasingly connected with global capital flows, this article focuses on the role of this retail concept in the process of metropolization. Using Lisbon and Fortaleza metropolises, we have developed a case study methodology to unfold the relationship between the spatial dissemination of shopping centres and the evolution of both metropolises. We have concluded that internationalisation of capital through investments in the shopping centres has produced urban-based impacts, visible both in the production of new centralities and in the consolidation of existing ones, which as a whole strengthens and enhances the metropolization of the studied areas.